2019
DOI: 10.1016/j.lwt.2018.11.092
|View full text |Cite
|
Sign up to set email alerts
|

Survival and development of Staphylococcus in egg products

Abstract: In this work, Staphylococcus has been employed to simulate a contamination of different egg foodstuffs. Liquid (egg white, egg yolk and whole egg) and also solid (Spanish potato omelette) products have been employed as model foods. The effect of different parameters, i.e. oxygen availability, cooking temperature and storage temperature, on microorganism survival and development has been evaluated. In addition, the structure of solid foods has been analysed by means of rheological measurements. Results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…These results are not in accordance with those found by Ananou et. al (2018) who reported that when S. aureus was incubated in liquid yolk at refrigerated temperatures the concentration of viable bacteria remained constant during 96 h. Similarly, and also in liquid yolk, Sanchez et al (2019) found that the concentration of S. warneri was approximately the same during 72 h at 11°C. This can be explained mainly by the different composition of the media, since the model pastry filling contained a high concentration of sugar that favoured microorganism growth.…”
Section: Effect Of Temperaturementioning
confidence: 93%
See 3 more Smart Citations
“…These results are not in accordance with those found by Ananou et. al (2018) who reported that when S. aureus was incubated in liquid yolk at refrigerated temperatures the concentration of viable bacteria remained constant during 96 h. Similarly, and also in liquid yolk, Sanchez et al (2019) found that the concentration of S. warneri was approximately the same during 72 h at 11°C. This can be explained mainly by the different composition of the media, since the model pastry filling contained a high concentration of sugar that favoured microorganism growth.…”
Section: Effect Of Temperaturementioning
confidence: 93%
“…The model food was prepared by mixing 100 g of sugar, 250 g of margarine and the preinoculum pellet resuspended in 20 g of raw egg yolk. The preinoculum was prepared from a refrigerated stock of Petri dishes as described in Sanchez et al (2019). Sterile 12 mL syringe-bodies (1:5 cm in diameter and 7:6 cm in length; HSW Norm-Ject) were packed with approximately 10 g of this inoculated medium, reaching inside 4 cm in height.…”
Section: Pastry Filling Preparation and Inoculationmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to its lower associated risk, S. warneri , an opportunistic pathogenic species of staphylococcus that has been isolated from eggs, has been employed as a surrogate for S. aureus (Neira et al ., 2019). Specifically, Staphylococcus warneri (CECT 236) acquired from the Spanish Collection of Type Cultures was employed as a model bacterium (Sanchez et al ., 2019).…”
Section: Methodsmentioning
confidence: 99%